Water detection in fuel tanks using the microwave reflection technique - Khalid, Kaida; Grozescu, Ionel Valeriu; Tiong, Lim Keng; Sim, Lee Teck; Mohd, Roslim (Institute of Physics Publishing, 2003)
Water is often present in fuel tanks due to night and day temperature changes, resulting in a build-up of condensed water within the inner surface of the tank. The expectancy of water infiltration in fuel tanks is even higher in flooding prone areas. Water settlement at the bottom of the tank causes internal corrosion. In this work, a simple, low cost and accurate microwave reflection type system for detection of water in fuel tanks has been developed. A module consisting of a microwave generator and a detecting diode is used to measure the microwave reflection coefficient at various positions through the fuel tank. In the course of the study, a motion control and data acquisition system has been developed. Software written using the Lab VIEW programming language is used to control the movement of the sensor and for the data acquisition. Theoretical and experimental results show the ability of the system to detect the presence of a water level down to approximately 1 mm. A simple theoretical model for power prediction of the reflected signal at various positions of the sensor in the tank is also presented.